2016
DOI: 10.14260/jemds/2016/772
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Uterine Bleeding in Perimenopause

Abstract: BACKGROUNDIn the peri-menopausal and post-menopausal women, 70% of the gynaecological problems are due to AUB. In the United States, 11% of the hysterectomies are performed for AUB per year. During climacteric, ovarian activity declines leading to anovulation or irregular maturation of follicles. Therefore, the menstrual cycles are often anovulatory and irregular leading to AUB. Prolonged anovulatory periods with unopposed oestrogen stimulation lead to endometrial hyperplasia. This increases the risk of endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Out of the study group, 76.5% women complained of menorrhagia, 15.6% with menometrorrhagia, 3.2% with polymenorrhea and oligomenorrhea each. In June 2016, Shivaji Neelgund et al [7] , in Pondicherry have done similar study and also found menorrhagia as common symptom in perimenopausal women. However they found that the next common symptom was metrorrhagia as compared to our study where menometrorrhagia was second most common symptom.…”
Section: Discussionmentioning
confidence: 61%
“…Out of the study group, 76.5% women complained of menorrhagia, 15.6% with menometrorrhagia, 3.2% with polymenorrhea and oligomenorrhea each. In June 2016, Shivaji Neelgund et al [7] , in Pondicherry have done similar study and also found menorrhagia as common symptom in perimenopausal women. However they found that the next common symptom was metrorrhagia as compared to our study where menometrorrhagia was second most common symptom.…”
Section: Discussionmentioning
confidence: 61%
“…Despite existing difference in study population, generally, menorrhagia is still the common type of bleeding in perimenopausal women with AUB. [ 34 35 36 ] Dilation and curettage by Karman cannula is considered as an adequate method for the hemorrhagic treatment and endometrial sampling biopsy, thus, almost cases underwent this interventional procedure in our study [ Figure 3 ]. [ 37 ] According to Gupta et al ., the use of Karman cannula resulted in less pain and is a much cheaper option in comparison to Pipelle.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically AUB manifests as menorrhagia, polymenorrhea, polymenorrhagia, metrorrhagia, menometrorrhagia, intermenstrual bleeding, etc. 6,7,8 When unscheduled bleeding occurs, especially if it is heavy or prolonged, further investigations such as trans-vaginal ultrasound and, hysteroscopy with biopsy if indicated, are needed. 9 The accuracy of endometrial biopsy for the detection of endometrial abnormalities has been reported to be as high as 96%.…”
Section: Discussionmentioning
confidence: 99%